Oscilloscope measurement of the synchronous phase shift in an electron storage ring - R. H. A. Farias (Physical Review Special Topics. Accelerators and Beams, 2001)
We present a new technique to measure the synchronous phase shift in an electron storage ring. A digital sampling oscilloscope is used to observe the cavity and beam signals simultaneously, and the amplitude and relative phase are obtained from a Fourier transform of the time-domain data. This procedure gives 6 mdeg resolution and is largely insensitive to input signal amplitude variations. The measurement system was used to study the dependence of the synchronous phase shift on beam current, gap voltage, and beam energy in the Brazilian Synchrotron Light Source electron storage ring.